2022
DOI: 10.3390/ijerph19116489
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of the First Wave of COVID-19 on Mental Health: Results from a Portuguese Sample

Abstract: The social conditions created by the COVID-19 pandemic had a great potential to affect the mental health of individuals. Meta-analyses indicate a rise in these problems in these periods among general populations, patients and health professionals, even with substantial heterogeneous results. This paper examines mental health impacts specifically during the first wave of COVID-19. An online survey was conducted with a Portuguese convenience sample (N = 1.062) comprising questions about substance use, perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Mental health problems related to the fear of COVID-19, social distancing measures (Piquero et al, 2021), and their consequences on daily life may also heighten perpetrator’s anger and loss of control, subsequently increasing the use of violence (Boxall et al, 2020). The substantial number of suicides and attempted suicides following IPF in 2020 and 2022 may indicate a significant impact of the COVID-19 pandemic on individuals’ mental health, both during and after the pandemic (Quintas et al, 2022; WHO, 2022). In addition, compared to the years before the pandemic, the prevalence of previous violence (i.e., before the lethal or near-lethal incident) was slightly lower, suggesting that some reported cases involved victims experiencing violence for the first time during the pandemic, consistent with earlier studies (e.g., Pérez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health problems related to the fear of COVID-19, social distancing measures (Piquero et al, 2021), and their consequences on daily life may also heighten perpetrator’s anger and loss of control, subsequently increasing the use of violence (Boxall et al, 2020). The substantial number of suicides and attempted suicides following IPF in 2020 and 2022 may indicate a significant impact of the COVID-19 pandemic on individuals’ mental health, both during and after the pandemic (Quintas et al, 2022; WHO, 2022). In addition, compared to the years before the pandemic, the prevalence of previous violence (i.e., before the lethal or near-lethal incident) was slightly lower, suggesting that some reported cases involved victims experiencing violence for the first time during the pandemic, consistent with earlier studies (e.g., Pérez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 11.7% reported moderate to severe levels of depression, 16.9% experienced similar levels of anxiety, and 5.6% classified their stress levels as moderate to severe. In addition, Quintas et al (2022) identified elevated levels of perceived stress and post-traumatic stress disorders during the COVID-19 pandemic. In their study involving 1,062 participants, 65% reported moderate levels of perceived stress, and 31.5% displayed symptoms consistent with post-traumatic stress disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation